2019
DOI: 10.1155/2019/1030256
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variant in the NF-κB Pathway Inhibitor NFKBIA Distinguishes Patients with Psoriatic Arthritis within the Spectrum of Psoriatic Disease

Abstract: Background and Aims The NF-κB pathway has been implicated in the genetic aetiology of psoriatic disease. However, since most patients with arthritis have psoriasis, discerning the genetic contributions to both aspects of psoriatic disease is not easy. Our aim was to study the association of common polymorphisms in genes of the NF-κB pathway in patients with psoriatic disease in order to dissect the contribution of this pathway in the appearance of each component (skin and joint) of the disease. Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Moderate evidence of a negative association was available for three markers: the presence of haplotype B*57-C*06 [ 97 , 99 ], the presence of HLA-C*06 [ 97 , 99 – 105 , 107 109 ], and the presence of the SNP rs2082412 in the IL12B gene [ 111 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moderate evidence of a negative association was available for three markers: the presence of haplotype B*57-C*06 [ 97 , 99 ], the presence of HLA-C*06 [ 97 , 99 – 105 , 107 109 ], and the presence of the SNP rs2082412 in the IL12B gene [ 111 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we do not know whether the genetic pathways to both cardiovascular comorbidity and psoriatic disease are common or different. However, a certain degree of commonality between psoriatic disease and some cardiovascular comorbidities as regards genes/proteins, biological processes, and inflammatory pathways has recently been highlighted [ 10 ]. Another study demonstrated shared genes between psoriasis and increased risk of dyslipidemia, hypertension, and cardiovascular disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rare NFKBIA rs7152376 C was significantly more frequent in PsA vs. controls (OR 2.03). The difference was even higher between PsA vs. “pure” psoriasis (OR 3.2) [ 33 ]. These findings are in line with the results of a meta-analysis that described the association of rs12883343, in complete LD with rs7152376, and the risk of PsA [ 34 ].…”
Section: Role In the Etiology Of Psoriatic Diseasementioning
confidence: 99%